Wykorzystanie social media marketing w odniesieniu do Pokolenia Z = The use of social media marketing in relation to Generation Z - Inków, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the era of accelerating technological development, the number of subscribers, users and advertisers using the Internet is growing. More and more often, researchers also emphasize that the Internet supports the effective promotion of a company and allows for building and strengthening relationships with customers.
Keywords: social media; social media marketing; pokolenie Z; Generation Z